Economic benefits of intergrated rice-fish farming in Bangladesh - Billah, Md Masum (2019)
The integration of quality rice (Oryza sativa L), a globally important staple food crop with fish Nile tilapia (Oreochromis niloticus) and common carp (Cyprinus carpio) is deemed more profitable than a mono-crop culture of the rice. Thus, this study was undertaken to determine the best stocking density, fertilization application, feeding schedule, feeding rate, feed premix and their effects on nutrients uptake, weeds control as well as fish and rice production in rice-fish integrated farming system. A series of experiments were conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University (BAU) in Mymensingh, Bangladesh from December 2017 to December 2018. In randomized complete block design (RCBD) with three replicates. Each plot was 15 m2 and surrounded by elevated dikes of about 0.5 m height. Rice (BR dhan29) seedlings were transplanted from the nursery to the plots at alternative row spacing of 15 and 35 cm and a spacing of 20 cm within the rows. Common carp and Nile tilapia were released 20 days after transplanting (DAT) at an average weight of 25.32±0.81 g and 12.52±0.48g and 1:1 mixing ratio with stocking density of 6 fishes/m2. The study determined a stocking density of 6/m2 in 1:1 of carp and tilapia was the best stocking density. In experiment (II), each treatment of fish species cultured with different doses of fertilizer as follows (T0) control: without any fertilization; (T1) with 100% recommended fertilizer (RF); (T2) with 75% recommended fertilizer (RF); (T3) with 10t h-1of compost fertilizer; (T4) with 5t h-1of compost fertilizer + 75% RF, and (T5) rice culture with 5 t h-1of compost fertilizer + 50% RF. The outcome shows that T4 9.72±5.35provided the maximum yield, followed by T5 9.72±5.35,T3 9.63±6.66, T2 9.45±6.32, T1 8.08±3.86 and T0 4.00±4.56 kg/m2. However, in experiment (III) it was found that feed application for five days a week in morning and evening (0900-1800) has the best rice yield11.96 t h-1 and straw yield 6.63 t h-1. Nevertheless, in experiment (IV) it was observed that feeding rate with 8% of body weight showed the highest production of rice and straw 5.35t h-1 and 6.59 t h-1. While in experiment (V) the addition of 10g feed premix in the feed improved the productivity of the carp 225.75g, tilapia 375.24g at 75 days after transplanting. A stocking density of 6 fishes/m2 at the ratio of 1:1 tilapia and carp; feeding five days morning (0900) and evening (1800) a week at 8% of body weight with 10g premix is recommended for carp and tilapia in the rice-fish farming system for better productivity and yield of rice.